Stability of nanoscale secondary phases in an oxide dispersion strengthened Fe-12Cr alloy - de Castro, V; Marquis, E; Lozano-Perez, S; Pareja, R; Jenkins, M (2011)
Transmission electron microscopy and atom-probe tomography were used to characterize on a near-atomic scale the microstructure and oxide and carbide phases that form during thermo-mechanical treatments of a model oxide dispersion strengthened Fe-12 wt.% Cr-0.4 wt.% Y2O3 alloy. It was found that some of the Y-rich nanoparticles retained their initial crystallographic structure but developed a Cr-enriched shell, while others evolved into ternary oxide phases during the initial processing. The Y- and Cr-rich oxide phases formed remained stable after annealing at 1023 K for 96 h. However, the number of Cr-rich carbides appeared to increase, inducing Cr depletion in the matrix. © 2011 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.